Veiled empire gender & power in Stalinist Central Asia - Northrop, Douglas Taylor (Ithaca : Cornell University Press, 2004)
Drawing on research in Russian and Uzbekistani archives, the author reconstructs the turbulent history of a Soviet campaign that sought to end the seclusion of Muslim women. He shows it as emblematic of the larger Soviet attempt to bring the proletarian revolution to Muslim Central Asia.
Embodying Uzbekistan -- Hujum, 1927 -- Bolshevik blinders -- The Chust affair -- Subaltern voices -- With friends like these -- Crimes of daily life -- The limits of law -- Stalin's Central Asia? -- Conclusion.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Women and communism -- Uzbekistan -- History -- 20th century; Muslim women -- Uzbekistan -- Social conditions -- 20th century; Veils -- Social aspects -- Uzbekistan -- History -- 20th century; Soviet Union -- Relations -- Uzbekistan; Uzbekistan -- Relations -- Soviet Union; Muslim women -- Social conditions; International relations; Veils -- Social aspects; Women and communism; Soviet Union; Uzbekistan; Frauenpolitik; Gleichberechtigung; Mittelasien; Kommunismus; Islam; Usbekistan; Vrouwen; Islam; Communisme; Frau; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Geschichte 1924-1941.; 1900-1999; History; Electronic books